“Eu não quero o lugar dos outros”: direitos e conflitos na Terra Indígena Cachoeira Seca - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2017)
This paper discusses the situation of poor peasants who occupy the Cachoeira Seca Indigenous Land and who settled in the area before the declaration of the IL. Beiradeiros whose occupation is intimately linked to the installation of rubber plantations and the exploration of rubber at the region of Terra do Meio. Settlers who stablished themselves in the area from the decade of 1980 in the midst of the opening of the Transamazônica and of the projects of colonization that settled in its margins. It is intended to show that the State’s action has created the conflicting scenario of Cachoeira Seca IL by giving different destinations to the same area and weaken the access to rights of settlers and riverside dwellers and the full realization of the territorial rights of the Arara, and mainly, by enabling as a result of uncertainty of the land situation of IL, the installation, appropriation and criminal exploration of Cachoeira Seca IL for others subjects, such as land grabbers and loggers. It is believed that the extrusion is essential to ensure the permanent possession and the exclusive use of IL’s natural wealth by the Arara and that it must follow the legally regulated protocol with a fair process of reallocation of the larger contingent of poor peasants who live there. This paper defends the integrity of the right of the Arara and its right to exclusive use of Cachoeira Seca IL and it is entirely against the invested for the disenfranchisement of any fraction of the IL.
Keywords: TI Cachoeira Seca; Camponeses; Extrusão; Realocação; CNPQ::CIÊNCIAS EXATAS E DA TERRA; BIOPROSPECÇÃO E MANEJO DE RECURSOS NATURAIS DA AMAZÔNIA